A history of the Venetian sacred solo motet (c. 1610--1720). - Rushing-Raynes, Laura. (The University of Arizona., 1991)
In 17th century Italy, the trend toward small sacred concertato forms precipitated the publication of a number of volumes devoted exclusively to sacred solo vocal music. Several of these, including the Ghirlanda sacra (Gardano, 1625) and Motetti a voce sola (Gardano, 1645) contain sacred solo motets by some of the best Italian composers of the period. Venetian composers were at the forefront of the move toward the smaller concertato forms and, to fulfill various needs of church musicians, wrote in an increasingly virtuoso style intended to highlight the solo voice. This study traces the development of the solo motet in the sacred works of Venetian composers from the time of Monteverdi to Vivaldi. It revolves around sacred solo motets composed at Saint Marks and the Venetian ospedali (orphanages). It includes works of Alessandro Grandi, Claudio Monteverdi, Francesco Cavalli, and Antonio Vivaldi. It also deals with solo motets of lesser composers whose works are available in modern critical and performing editions or in recently published facsimiles. In addition to providing a more detailed survey of the genre than has been previously available, this study provides an overview of highly performable (but largely neglected) repertoire.